Recycling of Photovoltaic Modules – A Strategy for Silicon and Metal Contact Recovery - Nerea Dasilva-Villanueva; Luis Jaime Caballero; David Fuertes Marrón; Araceli Rodríguez; Eduardo Díez; Jesús Ángel Muñoz Sánchez; Alejandro F. Braña; José Luis Plaza Canga-Argüelles; Enrique Cánovas; Carlos del Cañizo (SiliconPV Conference Proceedings)
As the installed capacity of photovoltaic (PV) systems continues to grow, also does the necessity to address the accumulating waste from decommissioned PV modules.  Millions of modules will need to be retired in the next few decades, and this poses a challenge that requires the development of cost-effective and efficient recycling strategies, with a focus on essential components such as solar cells, which are known for their significant environmental impact and energy budget. This study explores strategies to recover metal from front and rear contacts, as well as the potentiality of silicon substrate recrystallization. Alkaline-organic solutions allow for complete metal detachment with small-to-minimal silicon loss, and recrystallization of recovered substrates provides promising results in obtaining wafers suitable for the newly established industry requirements. Al-BSF solar cells fabricated from recycled materials exhibit improved performance, proving the feasibility of reclaiming precious metals and silicon substrates from PV modules. These encouraging first results represent an important step towards cycling PV systems within a circular economy framework, thereby minimizing waste and maximizing resource utilization.